Determinants of Intention to Adopt E-Wallet: Considerations for MSMEs Going Digital - Ari Apriani; Nur Endah Retno Wuryandari (Management Department Universitas Islam Negeri Sumatera Utara, 2022)
This study aims to determine whether MSMEs' intentions to adopt e-wallets are influenced by perceived ease of use, perceived risk, and promotion. Naturally, the findings of this study should be considered by MSMEs actors in their decision to adopt e-wallets and switch to digital payment methods because MSMEs must be able to adapt to conditions both during and after the pandemic by utilizing E-Wallet as a method of payment. This study relied on quantitative descriptive research to develop its concept, and previous studies carried out the research. The data that will be managed with the help of the Smart PLS tool will be distributed to a total of 250 respondent populations in the Jabodetabek area. The results of this study state that perceived ease of use and perceived risk have a positive and significant effect on the intention to adopt an e-wallet. In contrast, the promotion does not affect the intention to adopt an e-wallet. From the results of this study, it can be a consideration for MSME players to switch to digital and expand payment facilities with e-wallets that are easy to use and low risk so that consumers feel comfortable making payments.Keywords: E-Wallet, intention to adopt, MSMEs, perceived ease of use, perceived risk, promotion